2018
DOI: 10.3390/info9120293
|View full text |Cite
|
Sign up to set email alerts
|

Cloudification of Virtual Reality Gliding Simulation Game

Abstract: Cloud gaming provides cloud computing-based game as a service. In this paper we describe the development of a virtual reality base gliding game as a proof-of-concept. In the cloud, a cloud gaming platform is hosted on cloud servers with two principal components: game logic engaged in the implementation of game mechanics and game interactions, and video renderer that generates the game frames in real-time. The virtual gliding game was realized in the Unity gaming engine. To ensure smooth playability, and access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Especially through networking, the resource sharing of large scientific instruments can be realized, avoiding the repeated purchase and purchase of large instruments and equipment. e inverse kinematics problem of sports kinematics is the process of knowing the posture of the end effector of the moving human body and solving the motion speed and acceleration of each joint [20][21][22][23]. e process of finding inverse solutions in sports kinematics is a multisolution problem.…”
Section: Basic Eory Of the Virtual Experiments Systemmentioning
confidence: 99%
“…Especially through networking, the resource sharing of large scientific instruments can be realized, avoiding the repeated purchase and purchase of large instruments and equipment. e inverse kinematics problem of sports kinematics is the process of knowing the posture of the end effector of the moving human body and solving the motion speed and acceleration of each joint [20][21][22][23]. e process of finding inverse solutions in sports kinematics is a multisolution problem.…”
Section: Basic Eory Of the Virtual Experiments Systemmentioning
confidence: 99%
“…We decided to investigate what window size is best for VRET stimuli. A sliding window with a 1-s interval was applied to all collected signals with these window sizes in seconds: 3,5,8,10,13,15,18,20,23,25,28,29, and 30.…”
Section: Windowingmentioning
confidence: 99%
“…New advances in virtual reality (VR) technologies and high-quality consumer-grade devices [8] have opened up new prospects for virtual reality exposure therapy (VRET). VR systems for exposure therapy can offer reusable 3D environments and interactive scenarios for the feared stimuli that can be difficult to replicate in the real life, such as a virtual battle environment for post-traumatic stress disorder (PTSD) [9] or a virtual flying environment [10]. Moreover, a recent survey of VRET studies showed that it can be equally effective as in vivo exposure therapy and even has a slightly lower dropout rate compared to traditional treatment [11].We can improve and analyze VRET systems better by tracking the patient's physiological signals [12,13].…”
mentioning
confidence: 99%
“…However, during his paper presentation at the Search Engine Conference in 2006, Eric Schmidt used the world cloud computing for the first time as an approach to Software-as-a-Service (SaaS). It was used to analyze the business model of providing services over the Internet [3][4][5]. Cloud computing is regarded as a technique in which IT services are offered using low-cost computing units connected by Internet Protocol (IP) networks [6].…”
Section: Introductionmentioning
confidence: 99%